Cold cases: What we don't know about Saturn's Moons. (June 2018) - Buratti, B.J.; Clark, R.N.; Crary, F.; Hansen, C.J.; Hendrix, A.R.; Howett, C.J.A.; Lunine, J.; Paranicas, C.
Abstract: The Cassini -Huygens mission turned the moons of Saturn into tangible worlds. Although the discoveries from the spacecraft have been compiled in various review articles (e. g., Dougherty et al., 2009), there is no single publication that summarizes the remaining outstanding questions. Drawing on a workshop sponsored by the Cassini Project, we summarize the unanswered questions for the main icy moons of Saturn – Mimas, Enceladus, Tethys, Dione, Rhea, Hyperion, Iapetus, and Phoebe - for the disciplines of surface composition, geology, thermal properties, Enceladus's plume activity, interiors, and the interactions between Saturn's magnetosphere and the moons.